Digital Marketing pada Destinasi Wisata Minat Khusus: Sebuah Kajian Literatur Terstruktur dan Arah Penelitian Selanjutnya - Dalimunthe, Gallang Perdhana; Pratami, Ni Putu Nurwita; Bestari, Dinda Kayani Putri; Latifah, Ifa; Kurniawan, Ryan; Lisdayanti, Annisa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The internet has transformed into a powerful marketing tool to attract consumers. The limitations of service providers to reach potential visitors in introducing favorite destinations are the main reasons why digital marketing is used to get prospective customers. The purpose of this study is to explore the developing issue by focusing on the main question, namely how much research has been done so far regarding the use of digital marketing in special interest tourism destinations and what scope of research has the potential to be carried out in the future. This study uses a Systematic Literature Review (SLR) by identifying, selecting and analyzing various relevant research results in the form of descriptive and thematic reporting. The tool used to collect literature is Publish of Perish (PoP) which can sort literature from various databases, such as Google Scholar and Scopus. Based on the data that has been collected, as many as 83% of studies use qualitative analysis methods, this is based on the topic of digital marketing which is still relatively new in the context of tourism. Research on the topic of digital marketing in the context of tourism is still relatively rare, even so, digitalization and the development of information and communication technology make this topic inseparable from the dynamics of the tourism industry.